Trends and Limitations of Lignin as a Starting Material - Covinich, Laura Gabriela (2024)
This editorial envisions a future in which greater value is obtained from technical lignins. The amounts of currently available those lignins are immense, and the costs are often in line with lignin’s fuel value. Key challenges are associated with lignin’s complexity. When envisioning future prospects for lignin, it is important to consider any differences between different types of technical lignin as a starting material.